Land Acquisition for Public Interest: Balancing State Control and Individual Property Rights - Aarce Tehupeiory; Suwarno Suwarno; Ramisa Jahan; Mohit Islam (Unissula, 2024)
Land acquisition is essential for public development, but it often causes disputes over land rights and compensation when governments acquire land for economic and infrastructural projects. This research aims to address the challenges in land acquisition, particularly focusing on the shift from land “management” to land “ownership” in for public interest. The study seeks to highlight issues related to coercion, inadequate compensation, and the lack of proper consideration for individual landowners during the acquisition process. This study employs doctrinal research, using a combination of the statutory approach to analyze the balance between the State's control and individual property rights in land acquisition. The study finds that while land acquisition is legally grounded in principles of land control and protection for landholders, its implementation often fails to respect the rights of individual landowners. Issues of coercion and inadequate compensation persist, and the shift from land management to ownership in development activities exacerbates these problems. Simplifying the land acquisition bureaucracy while maintaining respect for land rights, fairness, and caution is essential for a more just and efficient process, aligning with principles of justice and proper compensation.